Best Answer

√3 - 9 is an expression, and so there is nothing to be solved.

It can be evaluated - use a calculator!

Q: Solve radical 3 minus 9

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

It is: -3-(6) = -9

Sobtract 1 from minus 9 and get minus 10.

-1/3 Make them into fractions like: 2/9-5/9 Then you just solve and you get -3/9 which reduces to -1/3

2√20 - 3√7 - 2√5 + 4√63 = 2√(4 x 5) - 3√7 - 2√5 + 4√(9 x 7) = 4√5 - 2√5 - 3√7 + 12√7 = 2√5 + 9√7

9*radical(3)/2 = 4.5*radical(3) = 7.794 approx.

Related questions

15

4x2 - 9 = (2x + 3)(2x - 3)

It is: -3-(6) = -9

Sobtract 1 from minus 9 and get minus 10.

-1/3 Make them into fractions like: 2/9-5/9 Then you just solve and you get -3/9 which reduces to -1/3

2√20 - 3√7 - 2√5 + 4√63 = 2√(4 x 5) - 3√7 - 2√5 + 4√(9 x 7) = 4√5 - 2√5 - 3√7 + 12√7 = 2√5 + 9√7

It is 5.098

9*radical(3)/2 = 4.5*radical(3) = 7.794 approx.

3 - 15/6 = 3 - 5/3 = (9-5)/3 = 4/3 = 1 and 1/3

7

minus 21 think of it as 12+9 which equals 21 then just whack a minus sign infront

y squared minus 9 (y*y)- 9 cannot be solved because there is no given value for 9.